Fat-free mass and gender influences the rapid-phase excess postexercise oxygen consumption - Lamont, L. S.; Romito, R.; Rossi, K. (Applied Physiology, Nutrition, and Metabolism, 2010)
The purpose of this study was to determine the influence of gender dimorphism and body composition on postexercise oxygen consumption during the rapid recovery phase. We compared the rapid-phase excess postexercise oxygen consumption (EPOC) in men and women matched for age (32.1 years), physical activity status, and maximal oxygen consumption (44.7 mL/kg.min), but not for body mass or fat-free mass (FFM). All subjects exercised for 1 h at 50% of their peak capacity. Although there were differences between genders in the magnitude of the absolute oxygen consumption and EPOC during the rapid phase of recovery, there were no differences found when EPOC was corrected for FFM. We conclude that the gender differences in the absolute O2 consumption and EPOC are related to the size of the FFM.